Effect of Baduanjin on postoperative activity tolerance, lung function and negative emotions in patients with lung cancer: a protocol for systematic review and meta-analysis - Jia Li; Zhening Liu; Daixi Wu; Huijing Dong; Yumin Zheng; Yulei Shen; Huijuan Cui (BMJ Open)
Introduction Patients who have undergone lung cancer surgery often experience reduced exercise tolerance, impaired lung function and increased negative emotions such as anxiety and depression. Baduanjin, a traditional Chinese mind-body exercise, has shown benefits in improving exercise tolerance and lung function in populations with chronic diseases. However, evidence on the effectiveness of Baduanjin for post-lung cancer surgery patients remains limited. This study aims to systematically assess the impact of Baduanjin on exercise tolerance, lung function and emotional well-being in these patients.Methods and analysis We will conduct a comprehensive search of PubMed, the Cochrane Library, China National Knowledge Infrastructure, Chinese Biomedical Literatures database, Wangfang database and China Science and Technology Journal Database (VIP) to identify randomised controlled trials (RCTs) assessing Baduanjin in postoperative lung cancer patients. The primary outcome measure will be the 6-minute walk test distance. We will assess the risk of bias in included RCTs using the bias risk assessment form from the Cochrane Collaboration Handbook. This protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-analyses Protocols 2015 guidelines.Ethics and dissemination Ethical approval is not required as no primary data are collected. The results will be presented at scientific conferences or submitted to a peer-reviewed scientific journal.PROSPERO registration number CRD42024570196.